2013
DOI: 10.1097/rli.0b013e3182778f07
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Pulmonary Perfusion in Emphysema

Abstract: Objectives: The objective of this study was to determine whether automated quantification of lung perfused blood volume (PBV) in dual-energy computed tomographic pulmonary angiography (DE-CTPA) can be used to assess the severity and regional distribution of pulmonary hypoperfusion in emphysema. Materials and Methods: We retrospectively analyzed 40 consecutive patients (mean age, 67 [13] years) with pulmonary emphysema, who have no cardiopulmonary comorbidities, and a DE-CTPA negative for pulmonary embolism. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
5
Order By: Relevance
“…Such relevancy has allowed that the advances in imaging techniques for lung perfusion and perfusion distribution become an attractive tool for diagnosis and outcomes prediction and evaluation. For example, differences in perfusion patterns measured by dual CT [29, 30] are being proposed for diagnosis of PH and even to differentiate pulmonary arterial hypertension (PAH) from chronic thromboembolic pulmonary hypertension (CTEPH) [31]. Recently, Lau et al [32] showed using SPECT/CT that pulmonary pre-capillary hypertension showed a redistribution of flow changing the gravidity influence, which appears as a potential tool for disease severity evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Such relevancy has allowed that the advances in imaging techniques for lung perfusion and perfusion distribution become an attractive tool for diagnosis and outcomes prediction and evaluation. For example, differences in perfusion patterns measured by dual CT [29, 30] are being proposed for diagnosis of PH and even to differentiate pulmonary arterial hypertension (PAH) from chronic thromboembolic pulmonary hypertension (CTEPH) [31]. Recently, Lau et al [32] showed using SPECT/CT that pulmonary pre-capillary hypertension showed a redistribution of flow changing the gravidity influence, which appears as a potential tool for disease severity evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In oncological imaging, the quantification of iodine has been used for the characterization of masses and for the assessment of therapy response [22]. The quantification of pulmonary iodine content has been shown to indicate the severity of pulmonary disorders including emphysema [23] and pulmonary embolism [24]. …”
Section: Discussionmentioning
confidence: 99%
“…No estudo de Sakamoto et al (19) , 72 pacientes com EP foram retrospectivamente divididos em 3 grupos de risco (baixo, intermediário e alto) e foi demonstrada diferença significativa no PBV global entre os grupos, enquanto o grupo de baixo risco não apresentou diferença significativa em relação aos pacientes com resultado negativo para EP. No estudo de Meinel et al (21) ,…”
Section: Perfusão Sanguínea Pulmonar Pela Tcde Na Epunclassified
“…A densidade média de iodo nos pulmões, em mg/ml, corresponde a quantidade total de iodo presente nos pulmões dividido pelo volume pulmonar. Para se obter uma estimativa relativa do volume sanguíneo perfundido por unidade de volume pulmonar, baseando-se no método aplicado em estudos anteriores (20,21) , a densidade média de iodo no parênquima pulmonar (mg/ml) foi normalizada pela densidade média de iodo no tronco da artéria pulmonar (mg/ml), sendo expressa em porcentagem (%) e definida pela equação: Os parâmetros PBVv e PBVm foram utilizados na análise regional dos lobos pulmonares e na análise global da perfusão sanguínea pulmonar.…”
Section: Pbvvunclassified
See 1 more Smart Citation